Voluntary Donations and Public Expenditures in a Federal System - Steinberg, Richard S. (American Economic Review, 1987)
Proponents of the new federalism argue that nonprofit organizations and local governments will fully offset federal social service expenditure cutbacks. The author analyzes this proposition as a competitive game in which donations are motivated by private and public good considerations. The author characterizes the response of political-economic equilibrium to exogenous changes in federal expenditures when local voters are cognizant of donor reactions. Partial replacement is the most likely outcome, though others are possible. Copyright 1987 by American Economic Association.